Efficacy of photodynamic therapy using 5-aminolevulinic acid-induced photosensitization is enhanced in pancreatic cancer cells with acquired drug resistance - Yiran Liu; Sally Kyei Mensah; Sergio Farias; Shakir Khan; Tayyaba Hasan; Jonathan P. Celli (Photodiagnosis and Photodynamic Therapy)
The use of 5-aminolevulinic acid (ALA) as a precursor for protoporphyrin IX (PpIX) is an established photosensitization strategy for photodynamic therapy (PDT) and fluorescence guided surgery. Ongoing studies are focused on identifying approaches to enhance PpIX accumulation as well as to identify tumor sub-types associated with high PpIX accumulation. In this study, we investigated PpIX accumulation and PDT treatment response with respect to nodule size in 3D cultures of pancreatic cancer cells (Panc1) and a derivative subline (Panc1OR), which has acquired drug resistance and exhibits increased epithelial mesenchymal transition. In monolayer and 3D culture dose response studies the Panc1OR cells exhibit significantly a higher level of photokilling at lower light doses than the drug naïve cells. Panc1OR also exhibits increased PpIX accumulation. Further analysis of cell killing efficiency per molecule of intracellular PpIX indicates that the drug resistant cells are intrinsically more responsive to PDT. Additional investigation using exogenous delivery of PpIX also shows higher cell killing in drug resistant cells, under conditions which achieve approximately the same intracellular PpIX. Overall these results are significant as they demonstrate that this example of drug-resistant cells associated with aggressive disease progression and poor clinical outcomes, show increased sensitivity to ALA-PDT.